Thermal engineering of nuclear power stations : balance-of-plant systems - Bowman, Charles F.; Bowman, Seth N. (Boca Raton, FL : CRC Press, 2021)
Thermal Engineering of Nuclear Power Stations: Balance-of-Plant Systems serves as a ready reference to better analyze common engineering challenges in the areas of turbine cycle analysis, thermodynamics, and heat transfer. The scope of the book is broad and comprehensive, encompassing the mechanical aspects of the entire nuclear station balance of plant from the source of the motive steam to the discharge and/or utilization of waste heat and beyond. Written for engineers in the fields of nuclear plant and thermal engineering, the book examines the daily, practical problems encountered by mechanical design, system, and maintenance engineers. It provides clear examples and solutions drawn from numerous case studies in actual, operating nuclear stations.
OCLC-licensed vendor bibliographic record.
Keywords: Nuclear power plants; Heat engineering; TECHNOLOGY / Engineering / Mechanical